Cenomanian-Turonian carbonate and organic-carbon isotope records, biostratigraphy and provenance of a key section in NE Sicily, Italy: Palaeoceanographic and palaeogeographic implications - Scopelliti, G; Bellanca, A; Erba, E; Jenkyns, H; Neri, R; Tamagnini, P; Luciani, V; Masetti, D (2008)
In eastern Sicily, a series of highly organic-rich black shales occur as exotic blocks (~ 100 m across) floating in tectonized sediments (Argille Varicolori Unit containing olistoliths of Cretaceous-Palaeogene age). A 19-metre section, through one of these blocks near the town of Novara di Sicilia, includes cyclically bedded black shales, marlstones and claystones, which have been dated using planktonic foraminiferal and nannofossil biostratigraphy. On this basis, the section is assigned to the latest Cenomanian and clearly represents a manifestation of the Oceanic Anoxic Event characteristic of that interval. Total organic-carbon values range up to 23% and the relatively high hydrogen indices record the presence of marine organic matter of low thermal maturity. High-resolution carbonate and organic-carbon isotope curves are comparable with those recorded elsewhere in indicating a significant positive excursion and confirm that, in the Novara di Sicilia section, the black shales are latest Cenomanian in age. By comparison with Cenomanian-Turonian black shales exposed elsewhere in Italy (Calabianca section, western Sicily; Livello Bonarelli, Bottaccione Gorge, Gubbio, Marche-Umbria), the section of Novara di Sicilia is different in being more stratigraphically expanded. However, this section from eastern Sicily does resemble extremely closely coeval sediments cropping out in Tunisia and Morocco. This association is taken as evidence that the Argille Varicolori Unit includes elements that were initially deposited on the north African shelf during Cretaceous time. © 2008 Elsevier B.V. All rights reserved.